The impact of a teacher development program for strategic reading on efl teachers’ instructional practice (2010)
Research on teacher development has been the focus of attention in recent decades. The overall aim of this study was to explore the impact of reading strategy training on high school teachers’ reading instructional practices. The study was conducted in the EFL context of Iran. To meet this aim, four EFL high school teachers voluntarily took part in the study. Teachers’ reading classes were observed and audio-recorded both before and after the teachers took part in a three-hour workshop on reading strategies. Drawing on data from observations, the results showed some degree of change in teachers’ reading practices after their having taken part in the workshops. That is, they took a more strategic approach to the teaching of reading in their classes. La investigación en el desarrollo profesional docente ha sido el centro de atención durante las últimas décadas. El objetivo general de este estudio fue explorar el impacto de la capacitación de profesores de secundaria en estrategias lectoras en las prácticas de enseñanza. Este estudio se realizó en el contexto del inglés como lengua extranjera en Irán. Para cumplir con este objetivo, participaron cuatro profesores de inglés como lengua extranjera de educación secundaria. Se observaron y grabaron sus clases enfocadas en lectura. Esto se hizo antes y después de participar en talleres de tres horas sobre el tema de estrategias lectoras. Los datos provenientes de las observaciones arrojaron como resultado que hubo cierto nivel de cambio en las prácticas de lectura de los profesores después de participar en los talleres. Es decir, adoptaron un enfoque más estratégico en sus clases.